Micro-Texture Evolution in Aggressive Machining of Al Alloy 7075. Issue 13 (2nd October 2016) - Tabei, A.; Shih, D. S.; Garmestani, H.; Liang, S. Y.
Abstract : The effects of process parameters on micro-texture evolution of Al alloy 7075 in machining under extreme conditions were investigated. For the first time, the process parameters in machining are related to the micro-texture evolution below the machined surface, through a computational modeling framework verified by robust experimentation. Finite element analyses (FEA) were performed to obtain the mechanical loads that the material experiences due to chip removal. The viscoplastic self-consistent (VPSC) approach was used to follow the evolution in texture due to the applied loads. The most outstanding texture component, which was seen in the case of increased feed rate, is closely followed by the texture evolution model. The observed discrepancy in experimental and computational results of texture evolution in a few studied cases is believed to be due to the activation of other microstructural evolution phenomena rather than dislocation slip, as a result of the ultra-high levels of exerted strain and strain rates to the machined surface.